Recurrence rate and lesions characteristics after cold snare polypectomy of high‐grade dysplasia and T1 lesions: A multicenter analysis. Issue 12 (27th July 2021) - Yoshida, Naohisa; Fukumoto, Kohei; Hasegawa, Daisuke; Inagaki, Yoshikazu; Inoue, Ken; Hirose, Ryohei; Dohi, Osamu; Ogiso, Kiyoshi; Murakami, Takaaki; Tomie, Akira; Okuda, Kotaro; Inada, Yutaka; et al.
Abstract: Background and Aim: High‐grade dysplasia (HGD) and T1 lesions are accidentally resected by cold snare polypectomy (CSP) and the characteristics, and follow‐up of them has not been reported. In this study, we analyzed the histopathological findings and recurrence of them. Methods: This was a multicenter retrospective‐cohort study. We collected HGD and T1 lesions of ≤ 10 mm resected by CSP among 15 520 patients receiving CSP from 2014 to 2019 at nine related institutions, and we extracted only cases receiving definite follow‐up colonoscopy after CSP of HGD and T1 lesions. We analyzed these tumor's characteristics and therapeutic results such as R0 resection and local recurrence and risk factors of recurrence. Results: We collected 103 patients (0.63%) and extracted 80 lesions in 74 patients receiving follow‐up colonoscopy for CSP scar. Mean age was 68.4 ± 12.0, and male rate was 68.9% (51/80). The mean tumor size (mm) was 6.6 ± 2.5, and the rate of polypoid morphology and rectum location was 77.5% and 25.0%. The rate of magnified observation was 53.8%. The rates of en bloc resection and R0 resection were 92.5% and 37.5%. The local recurrence rate was 6.3% (5/80, median follow‐up period: 24.0 months). The recurrence developed within 3 months after CSP for four out of five recurrent cases. Comparing five recurrent lesions to 75 non‐recurrent lesions, a positive horizontal margin was a significant risk factor (60.0% vs 10.7%, P < 0.001). Conclusions: High‐grade dysplasia and T1 resected by CSP were analyzed, and the local recurrence rate of them was substantially high.